Bentuk dan Fungsi Kearifan Lokal Cerita Rakyat Waisalaka di Negeri Waai - P. J. Pattiasina; Martha Maspaitela; Chelsy Cherly Gommies (Journal on Education, 2024)
Local wisdom contained in folklore is passed down from generation to generation without a clear author. Folklore contains many moral messages such as good manners, mutual love and helping others. One of the researchers used a qualitative descriptive method. This research data collection technique uses reading and note-taking techniques. Based on the results of research and analysis regarding the form and function of local wisdom in Waaisalaka folklore in Waai Country. This research aims to describe the form and function of local wisdom in Waaisalaka folklore in Waai Country to maintain a harmonious relationship between society and nature. Local wisdom is closely related to culture, which is a reflection of each region, created and transmitted orally and preserved and passed down from generation to generation. The function of local wisdom is divided into two parts, namely peace and prosperity. Peace includes harmony, justice, commitment and responsibility, social solidarity, harmony and tolerance, caring, positive thinking, and gratitude. Meanwhile, welfare is craft, discipline, hard work, creativity and innovation, mutual cooperation or cooperation, gender management, conservation and caring for the environment. Local wisdom of areca nut, water and spear. With a total of eleven comfort functions and six wellbeing functions. In the Waisalaka Folklore in Waai Country, there are three local wisdoms, this must be something serious to be addressed again.